3x+2y/4=2x+y/5=x-y+1/6
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 09:31:17
3x+2y/4=2x+y/5=x-y+1/63x+2y/4=2x+y/5=x-y+1/63x+2y/4=2x+y/5=x-y+1/63x+2y/4=2x+y/5可得x=-3y/10x-y+1/6=2x
3x+2y/4=2x+y/5=x-y+1/6
3x+2y/4=2x+y/5=x-y+1/6
3x+2y/4=2x+y/5=x-y+1/6
3x+2y/4=2x+y/5 可得 x=-3y/10
x-y+1/6=2x+y/5 x=-6y/5+1/6
-3y/10=-6y/5+1/6 y=5/27 x=-1/18
分成两个等式;3x+2y/4=2x+y/5 和 3x+y/5=x-y+1/6 联立求得 x=-1/18 y=5/27
3x+y/2=2x+y/5,则x=-3y/10,代入得3x+y/2=-9y/10+y/2=-2y/5=-3y/10-y+1/6=-13y/10+1/6,y=5/27,x=-1/18。
3x+2y/4=2x+y/5 2x+y/5=x-y+1/6
x=-3y/10 x=-6y/5+1/6
9y/10=1/6
y=5/27 x=1/18
化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1
3(x+y)+2(x-y)=36 4(x+y)-5(x-y)=2
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27
(x-y)/(x+y)=3求( 3x-2y-1)/(x+y-5)
先化简再求值(x-y)(x-2y)+(x-2y)(x-3y)-2(x-3y)(x-4y) x=4 y=5
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?
x+y+2(-x-y+1)=3(1-y-x)-4-(y+x-1),x+y=?
{x+y=1 ,xy=-6{x(2x-3)=0,y=x²-1{(3x+4y-3)(3x+4y+3)=0,3x+2y=5{(x-y+2)(x+y)=0,x²+y²=8{(x+y)((x+y-1)=0,(x-y)(x-y-1)=0
先化简 再求值 (2x-y)(y+x)-(x-2y)(2y+x)-(-3y+x)^2其(√x+1)+y^2+4=-4y
已知x-y=1,求[(x+2y)^2+(2x+y)(x-4y)-3(x+y)(x-y)]除以y的值大神们帮帮忙
已知x-y=1,求[(x+2y)²+(2x+y)(x-4y)-3(x+y)(x-y)]÷y的值
3x-2y=1 4x-5y
(x-y)/4+(x+y)/5=1/4 (x+y)/9-(x-y)/3=//2(x-y)/4+(x+y)/5=1/4(x+y)/9-(x-y)/3=//2